Ethnic disparities in the relationship between the number of chronic diseases and health status among adults aged ≥45 in Yunnan Province, China - Rui Deng; Rui Deng; Rui Deng; Jie Chen; Xinping Wang; Xinping Wang; Xinping Wang; Yan Xiao; Ying Chen; Ying Chen; Ying Chen; Chaofang Yan; et al. (Frontiers in Public Health)
BackgroundChronic conditions among middle-aged and older adults from ethnic minority backgrounds is becoming increasingly prominent, while there is limited evidence available regarding the influence of NCDs on ethnic minority groups in later life. This study aims to examine the characteristics of NCDs and health status among adults aged ≥45 in multi-ethnic settlement, as well as explore the disparate impacts of chronic condition on ethnically diverse populations.MethodsThis cross-sectional study was conducted in Yunnan Province, China from July to December 2022. Intergroup comparisons were performed using chi-square tests and Kruskal-Wallis H test. Multivariable linear regression and Tobit regression were used to assess the impact of NCDs on health status indicators.ResultsOut of the total 2,710 participants, approximately 57.90% exhibited at least one NCD, with individuals from the Han majority exhibiting a higher prevalence (p < 0.001). Individuals belong to Zhiguo ethnic minority groups had higher mean scores for ADL (15.92, SD = 3.80), chronic pain (2.27, SD = 2.28), and frailty (3.37, SD = 2.61). A significantly negative association was observed between the number of NCDs and the health utility value across all ethnic groups (p < 0.001). Conversely, there was a positive relationship between scores for chronic pain and frailty with the number of NCDs for all three ethnic groups respectively; within Zhiguo ethnic minority groups alone, there was also a positive correlation between ADL scores and the number of NCDs (p < 0.001).ConclusionThe prevalence of NCDs among adults aged ≥45 in Yunnan province is significantly higher, indicating a substantial burden of NCDs in underdeveloped areas. Although the chronic condition is more prominent among Han majority, individuals belonging to Zhiguo ethnic minority exhibit poorer health outcomes. And the negative health effects from NCDs to health status are more severe among ethnic minority groups, indicating an urgent need for targeted interventions to address health disparities in multi-ethnic regions.